A criação vocabular em blogs : motivações e análises - Panichella, Fernanda Callefi (2014)
This Dissertation has as main objective the analyze the occurrence of neologisms in three blogs of the southern region in Brazil - corresponding to the states of Paraná (PR), Santa Catarina (SC) and Rio Grande do Sul (RS) - with systematic research on the neological research tables. We also showed the issues that are most likely to product neologisms, the most prevalent class of words for the formation of neologisms and the type of neology most encountered. The so called "e- communication" formations will be examined in order to approach these creations for speech, studying formations such as lexicons, since they do not imply only the production of a new antropocultural perspective and correspondent language unity, but also to an answer to those sociocultural needs. The program Microsoft Word is used as a tool for the corpus manipulation, it was possible to store the corpus from the three blogs in the period of the day 13/02/2012 until 13/02/2013, but also, with the aid of the program, the number of occurrences in posts of bloggers was found through the find tool, which identified the requested neologisms and thus it was possible to detect how many times particular neologism appeared on each blog. Our study shows 37 neologisms used by bloggers that were analyzed in neological tables, of which 29 occurrences belong to the blog that represents the state of PR, 7 of them were neologisms produced in blog representing SC and 1 was found in the blog representing the State of RS. After this procedure, we analyzed the number of occurrences of these neologisms counting the number of occurrence of bloggers and the number of occurrences of posts from readers, resulting in 120 neologisms. Among them, 77% were found in the blog that represents the state of PR, 22% from the SC blog and only 1% in the blog that represents the RS. Politics and football were the topics that most favored the use of neologisms. It also appeared that neologisms are used both to denounce, criticize, satirize or even to name something. In addition, the nouns was the most recurrent class of words to the formation of neologisms. Finally, the prevailing neology was the stylistic due to the blog genre that requires increasingly creative messages to, thereby, attract readers.